آراء ابن منظور النحوية من خلال الشواهد القرآنية في معجم لسان العرب - موساوي, مصباح; زتون, خرف (جامعة الوادي - University of Eloued, 2020)
اعتنى ابن منظور عناية فائقة بعلوم النحو، ونظرا لعلاقة النحو بالقرآن، وأن اختلاف الحركات الإعرابية التي تعتري أواخر الكلمات لها علاقة مباشرة في اختلاف دلالاتها القرآنية بحسب السياق القرآني، فإن دراسة اختلاف الحركات هي مهمة علم النحو، ليتوصل به إلى معرفة وإدراك معاني وأسرار القرآن، وتهدف هذه الدراسة إلى إبراز جانب من جوانب جهود ابن منظور في حفظ اللغة، حيث تبين بعد عملية الاستقراء أن ابن منظور كانت له آراء نحوية تبرز من خلالها أراءه وآراء علماء اللغة، وقد تناولنا نماذج من معجمه توحي بأن له دراية وفقها بعلوم اللغة، فقد أشار في الشواهد القرآنية خاصة، إلى المبتدأ والخبر، والتوابع والمنصوبات، ونواصب الفعل المضارع، وشرح بعض حروف النصب، وحروف الجر ومعانيها، واستعمالات حرف (الواو) في القرآن، والشواهد القرآنية في الفعل اللازم والمتعدي، وهكذا نجد أن ابن منظور لا تفهم معاني الآيات القرآنية عنده إلا بتوفيتها حقها من الإعراب، وخلصنا إلى أن ابن منظور قد وافق كثيرا من علماء النحو في الشواهد القرآنية التي أوردها في معجمه، إلا أنه يميل كثيرا إلى الجانب اللغوي في التفسير.. Abstract: Ibn Manzoor paid close attention to grammar, as it is related to Koran and as the difference in diacritical marks at the words’ endings are directly related to the different significance of the Koran according to its context. The study of the different marks is the task of grammar, in order to know and understand the meanings and secrets of the Koran. This research aims to highlight some aspects of Ibn Manzoor's efforts in securing the language. Through extrapolation, we found that Ibn Manzoor had grammatical views through which his views and those of linguists emerged; We have examined models from his dictionary Lisan El-Arab that suggest that he is familiar with language sciences. He pointed out in the koranic evidences particularly to the subject and the predicate of the nominal sentence, the appositions, the accusatives, the subjunctivals of present tense, explaining the accusatives, the prepositions and its meanings, the use of the letter " و " in the Koran and also the transitive and intransitive verbs. We found that Ibn Manzoor thought that the meanings of Koranic verses could not be understood without treating its grammar exhaustively. Our study results that he agreed many grammarians in koranic evidences mentioned in his dictionary but he tends to the linguistic interpretation.
مقال
Keywords: آراء، ابن منظور، التوابع، التهويل والتفخيم، حروف الجر، القرآنية، الشواهد النحوية، المتعدي، العطف، لسان العرب; Grammatical Views; Ibn Manzoor; Evidences; diacritical marks; Lisan El-Arab Dictionary